The Nation’s ‘Other’ Housing Project - Zihao Wong (Footprint)
Singapore’s privatised high-rise housing landscape is the nation’s ‘other’ housing project, emerging alongside the city-state’s dominant narrative of its successful public housing project since the 1970s. Unique to Singapore’s privatised high-rise housing developments was the intervention of the state in the close regulation of scarce land. Singapore’s private high-rise housing developments thus reflect a nation’s attitude towards its land as resource, and its subsequent imaginations and productions of more ‘land’ in the construction of high-rise housing estates. State intervention also maximised these housing developments as part of wider national aspirations to the status of a global city, and for its citizens, a ‘green and gracious’ Singaporean society. Taking the Pearlbank Apartments and the Pandan Valley Condominium as two key developments of Singapore’s emerging private high-rise housing landscape in the 1970s, this article examines the production of the nation’s aspirational housing in the confluence of Singaporean state-led vision and a people’s housing aspirations.